Inter. Algebra
 👍 0
 👎 0
 👁 54
Respond to this Question
Similar Questions

Inter. Algebra
Count Iblis what is the answer to 2 square root sign 18x? The instructions say to simplify or reduce. 2*(18x)1/2= 2*(9*2)1/2= 2*3(2)1/2= 6*(2)1/2 If you can leave it in this form, the above is the way to end. If you are to
asked by Andrea on December 2, 2006 
Algebra 2
I had to solve this quadratic equation using the complete the square method. Did I do it correctly? The problem is 3x^2+18x+10= 0 (3x^2+18x+10)/3= 0/3 = x^2+6x+(10/3)=0 x^2+6x+(10/3)(10/3)=0(10/3) =x^2+6x= (10/3( x^2+6x
asked by Keith on October 18, 2015 
math
Nakim simplified 3 times the square root of 2x plus x times the square root of 8x minus 5 times the square root of 18x and got 10x times the square root of 2x for an answer. Part 1: Using complete sentences, explain what Nakim
asked by kidd on July 9, 2013 
math
solve for x x^2+18x+4=0 is the answer 18 + or square root symbol 90
asked by Allison A on November 22, 2011 
Algebra
checking problem Use FOIL to multiply: (6x – 1)(3x – 4) 6x*3x + 6x*(4) + (1)*3x + (1)*(4) = 6x*3x = 18x^2 6x*4 = 24x 1*3x = 3x 1* 4 = 4 18x^2 – 24x 3x +4 = 18x^2 – 27x + 4
asked by John on October 22, 2007 
math
when I have (2x^(3)18x)(2x^(3)) / (x^(2)9) am I suppose to be left with 18x/(x^(2)9) or is it just 18x? Please help and thanks!
asked by Blair on July 29, 2008 
Pre Calculus
Write f(x) =x^311x^2+18x+32 in the form f(x)= (xk) q (x) +r when k=6 + (square root)6, and demonstrate that f(k)=r
asked by Jessica Maths on July 4, 2016 
math!
determine two geometreic sequences whose first terms are 18x9, 2x+8 and x1 how would I go about and do this question? I have no idea! so a little help would be really helpful! thanks! A geometric sequence looks like a, ar, ar2,
asked by Anonymous on October 18, 2006 
calculusanswer check
Deermine the derivative of f(x)=[(3x^2+1)^3+1]^2. Express your answer in simplified form. For this I got 54x^6+162x^5+54x^4+108x^3+18x^2+18x+2
asked by Kim on May 9, 2014 
Inter. Algebra
I find it curious here: a  b=2 in this case, rationalize by multplying both sides by a+b, getting ab=2 a^2b^2=2(a+b) 2x+3x+2=2(a+b) (x+5)/2 = a+b now add the original equation.. 2= ab or 2a= 2+ x/2 + 5/2 4sqrt(2x+3)= x+9
asked by bobpursley on December 3, 2006